Antigen presenting subset of СD66b+CD16+CD33+HLA-DR+ neutrophilic granulocytes in acute osteomyelitis in children: Immunomodulating effects of immunotropic hexapeptide in an in vitro experimental system - I. V. Nesterova; G. A. Chudilova; Yu. V. Teterin; E. A. Chicherev; V. N. Chapurina; M. N. Mitropanova (Медицинская иммунология, 2023)
Inclusion of neutrophilic granulocytes (NG) in inflammation depends on the expression of receptors providing the functions of NG. Acute osteomyelitis (AOM) occupies a central place among purulentinflammatory diseases in children. AOM purulent-necrotic process proceeds in the bone, bone marrow – the site of hematopoiesis. It is interesting to determine the functionally significant NG subsets, their phenotype in OM and evaluate the effect of immunotropic substances for the correction of dysfunctions. Aim: to specify the variants of changes in quantitative and phenotypic characteristics of CD66b+CD16+CD33+HLA-DR-, CD66b+CD16+CD33+HLA-DR+ NG subsets at AOM in children and evaluate the possibility of their immunomodulation under the influence of hexapeptide (HP) – Arginyl-alpha-Aspartyl-Lysyl-Valyl-Tyrosyl-Arginine in vitro.Peripheral blood (PB) of 24 children 8-15 years old AOM were the study group (SG). The comparison group (CG) – 13 healthy children. HP (10-6 g/L) were incubated with PB SG (60 min, 37 °C) to evaluate the effects (SG1). The number of NG subsets CD66b+CD16+CD33+HLA-DR+, CD66b+CD16+CD33+HLA-DR- (FC500, Beckman Coulter, USA), receptor expression density (MFI), phagocytic activity before and after incubation with HP were determined.The NG subset expressing HLA-DR – 29.9 (18.4-43.6) % CD66b+CD16+CD33+HLA-DR+ was registered in children with AOM. The number of CD66b+CD16+CD33+HLA-DR+ was 1.5 times lower (p > 0.05), of CD66b+CD16+CD33+HLA-DR+ was 1.2 times higher (p > 0.05) than before incubation with of HP. The redistribution of subsets apparently occurs due to the binding of HPs to HLA-DR on the NG membrane. Also MFI HLA-DR was low (p > 0.05); the 1.3-fold increase in MFI CD66b, 1.4-fold decrease in MFI CD16 were revealed (p < 0.05).The study was the first to demonstrate the presence of NG subset of CD66b+CD16+CD33+HLA-DR+ in the PB of children with AOM. Subset of CD66b+CD16+CD33+HLA-DR+NG in AOM indicates the appearance of an activated subset of NG in PB with the properties of APC. The positive influence of HP on the phenotypic characteristics of subsets СD66b+CD16+CD33+HLA-DR-, СD66b+CD16+CD33+HLA-DR+. Restoration of phagocytic function of NGs under the influence of HP is connected with the increase of CD66b expression, which influences the effector function of NGs and decrease of CD16 molecule hyperexpression that stipulates decrease of damaging cytotoxic activity of NGs.